A governança das Redes de Atenção à Saúde nos territórios microrregionais - um estudo de caso - Romulo Batista Gusmão (2022)
The contemporary world is marked by complexity. Collaborative arrangements, within the scope of public policies, are therefore necessary in the face of the challenge of delivering results to the citizen. In health, the Health Care Networks (RAS) are the coherent social response to the current epidemiological context of an increase in chronic diseases. It is a model potentially capable of favoring comprehensive health systems, based on collaborative networks, formed by a complex operational structure, requiring different articulations and specific governance processes. As a management driver, governance is essential, given the diversity of stakeholders, institutions and relationships that are involved to deliver value in health. However, it still presents itself as an emerging, theoretical approach, whose processes, operational applicability and effects on the daily life of regional territories, within the scope of RAS, are still poorly researched. More analytical works are scarce in the literature and have a low degree of precision in the discussion and explanation of the limitations that limit their effectiveness and impact on the results of the RAS. The objective of this work is, therefore, to describe the governance processes of the maternal-infant network in the micro-region of Governador Valadares – East of Minas Gerais, and their respective weaknesses. Therefore, a single case study was used as a methodology, with a qualitative approach and exploratory character. Semi-structured interview, document analysis, and Focus Group were used for data collection, worked later with the content analysis technique. It was evidenced in the results that the micro-regional governance of the RAS is a challenging element of its operational structure, whose locus is dispersed, both in its internal and external environment, with diversified processes, frankly fragmented / disarticulated, making it, therefore, , superficial, incoherent and out of context, assuming a notary, reactive and episodic character. The low degree of legitimacy of regional actors in decision-making processes, and a “focused financing” policy structuring logic, to the detriment of regional loco needs, are potentiators of fragility. Even so, collaborative governance is favored due to the initial experiences of local actors; especially in its procedural and contractual component, through frequent municipality-state interaction, as well as the availability of elements that induce such processes in the national context. There is, however, a strong need to foster a culture of regional governance, for the RAS, more consistent / robust, guided by the bias of complex phenomena, typical of process-territories, in fact recovering its locus of occurrence, protecting legitimacy to the actors in the situation, in order to favor cycles of continuous improvement, opening space, therefore, for the appropriation and reinvention of the subjects at stake.